Whiteflies of Belize (Hemiptera: Aleyrodidae)Part 2óa review of the subfamily Aleyrodinae Westwood - Martin, Jon H. (Zootaxa, 2005)
A field survey of Sternorrhyncha (Hemiptera) in Belize, principally conducted within the Chiquibul Forest Reserve (CFR), has revealed almost 200 species of whiteflies, all but 40 of them belonging to the subfamily Aleyrodinae. Provided here is an illustrated account of described Belize species of Aleyrodidae-Aleyrodinae. This account proposes three new generic synonymies, three new specific synonymies, nine ten combinations, one revalidated species and provides descriptions of three new genera and 12 new species. Two appendices are provided: a check list, which includes species remaining undescribed, and the associated host-plant genera or families (when known) of all putative species; and a summary of taxonomic changes proposed here. Line drawings and/or photographs of slide-mounted puparia are provided for all described species, and photographs alone are provided for a few of the more distinctive species that remain undescribed.